Management Strategies To Improve The Accreditation Of The Sharia Accounting Study Program (A Case Study At FEBI UIN North Sumatra Medan) - M. Fauzan; Ananda Anugrah Nasution (Jurnal Ekonomi, 2024)
The general objective of this research is to analyze the efforts that have been made by the Faculty of Islamic Economics and Business at UIN North Sumatra Medan to improve the accreditation of the Sharia Accounting study program, to provide solutions to the problems faced regarding management strategies in the Sharia Accounting study program at UIN North Sumatra Medan, and to analyze the level of success in planning, implementing, and applying management strategies in the Sharia Accounting study program at UIN North Sumatra Medan. This research adopts a qualitative descriptive method. The subjects of this research include the Dean, Deputy Dean, Head of Department/Study Program, students, alumni, and stakeholders of the Faculty of Islamic Economics and Business at UIN North Sumatra Medan. The data analysis technique used in this research is SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats). The results of the research show that the management strategies implemented by State Islamic Universities (PTKIN) in North Sumatra to improve the accreditation of the Sharia Accounting Study Program should be tailored to the results of each institution's SWOT analysis. UIN North Sumatra Medan can adopt an aggressive strategy that leverages existing strengths and opportunities to accelerate accreditation improvement. Meanwhile, UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan must focus on a turn-around strategy by addressing internal weaknesses. The implementation of appropriate strategies, along with the application of sharia management principles, will encourage the study program to become more competitive and of higher quality in the future. Based on the SWOT analysis, the recommended management strategies for improving the accreditation of the Sharia Accounting Study Program at PTKIN in North Sumatra focus on utilizing internal strengths such as international collaboration, faculty networks, and physical facilities, while maximizing external opportunities through cooperation with industry and sharia financial institutions. The S-O and S-T strategies emphasize the importance of strengthening international collaboration and networks to compete in the global market and address external threats.